Comparison of Dectomax and Valbazen on beef cattle carcass traits - J.A. Christopher; T.T. Marston; J.R. Brethour; Gerald L. Stokka (Kansas Agricultural Experiment Station Research Reports, 2006)
The objective of this trial was to determine if types of dewormers affected carcass characteristics. Crossbred steers (n=428) were stratified by weight and ultrasound marbling score and administered either Dectomax (subcutaneous injection) or Valbazen (oral) dewormer. Fecal egg counts indicated that both dewormers cleared internal parasites from the cattle. Carcass data indicated that Dectomax increased fat deposition as measured by 12th rib back fat; kidney, pelvic, and heart fat; and marbling score, when compared with Valbazen. Deworming products may affect carcass traits that are used to value cattle.
Keywords: Cattlemen' s Day; 2006; Kansas Agricultural Experiment Station contribution; no. 06-205-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 959; Beef; Dectomax; Valbazen; Carcass traits